Implementasi Metode Entropy dan Topsis Dalam Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik - Mitha Anggreani Rupang; Adhi Kusnadi (Ultima Computing : Jurnal Sistem Komputer, 2018)
Employee is a part of the company's most important asset in its efforts to maintain survival, growth, ability to compete and profit. At this time the process of assessment of employees in Jakarta Smart City is still in the form of manual and the decision only from one party only, so the process is still not accurate. So it takes the methods that must be able to replace that system. For that reason, a Decision Support System (SPK) was created to determine the best employees in Jakarta Smart City. In the system implemented the method of Entropy and TOPSIS. Entropy method can be trusted in determining the weight of the criteria to be used. And TOPSIS method can quickly perform the ranking process. Criteria to be used are quality and quantity of work, obedience, cooperation, morale, and work discipline. The index of satisfaction level of respondents to the decision support system ranges from 70% -80%, meaning that the assessment of the system created gives results at a fairly good level. Index Terms—employee, nter key words or phrases in alphabetical order, separated by commas